180k views
2 votes
4(x - 6) + 2 = 6x -2
solve the equation

User Cyrill
by
5.2k points

2 Answers

6 votes

Answer:x=-10

Step-by-step explanation:4x-24+2=6x-2 -22+4x=6x-2 , 2x=-20 , x=-10

User Ryan Z
by
5.6k points
3 votes

Answer:

x=−10

Explanation:

Let's solve your equation step-by-step.

4(x−6)+2=6x−2

Step 1: Simplify both sides of the equation.

4(x−6)+2=6x−2

(4)(x)+(4)(−6)+2=6x+−2(Distribute)

4x+−24+2=6x+−2

(4x)+(−24+2)=6x−2(Combine Like Terms)

4x+−22=6x−2

4x−22=6x−2

Step 2: Subtract 6x from both sides.

4x−22−6x=6x−2−6x

−2x−22=−2

Step 3: Add 22 to both sides.

−2x−22+22=−2+22

−2x=20

Step 4: Divide both sides by -2.

−2x

−2

=

20

−2

x=−10

User Asksol
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.